Adaptation and coping of people who underwent brain tumor surgery: literature review - García-Meza, Carlos Francisco (Universidad de Sonora, 2019)
Introduction: The return of people to everyday life after brain tumor surgery impacts their biological, social, psychological, environmental, and spiritual life. Objective: The objective of this study is to assess the current scientific evidence related to the adaptation and coping process experienced by people who have survived neurological surgery due to brain tumor. Methods: A systematic search of the scientific evidence published in English and Spanish was carried out from 2009 to 2017 in databases such as PubMed, Scielo, and Google Scholar, using the keywords “adaptation”, “coping”, “Roy’s model”, “brain tumor”, and “surgery”. The inclusion criteria were set forth according to the questions raised. From a total of 75 articles found, 15 were selected; those that met the inclusion criteria. Results: The systematic reviews, quasi-experimental, qualitative narrative and descriptive, present evidence of cognitive deterioration, deterioration of quality of life, anxiety, physical limitations and stress, in some instances in the long term regarding survivors of brain tumor such as meningiomas and gliomas. One intervention study that used the adaptation and coping model, regarding improvement of quality of life, is reported. Conclusions: The literature shows diverse forms of adaptation and coping to everyday life after surgery, also showing physical and psychological complications. It is suggested to carry out studies that inform about nursing interventions necessary to provide holistic care, based on the experiences of people who go through these experiences.